Examining the Support of Modern Athletic Reform Proposals Developed by the Coalition on Intercollegiate Athletics in Response to Higher Education Athletic Reform: A Case Study - Wade W. Zimmerman; Leah E. Wickersham (Arizona State University, 2013)
This study was conducted to determine the success for the diffusion of the Coalition on Intercollegiate Athletics (COIA) white paper Framing the Future: Reforming Intercollegiate Athletics. The Stages of Concern Questionnaire (SoCQ) and personal interviews were utilized to collect data and purposeful sampling was used to identify one NCAA Division I university in the state of Texas. Athletic personnel and faculty senate members were asked to complete the SoCQ and participate in an interview for the study. Findings provide evidence that the participants share common concerns in relation to the adoption of the COIA white paper such as creating a balanced approach to academics and athletics, increasing campus pride, and academic integrity. Participants also felt that meaningful collaboration among faculty and staff members can prove beneficial to helping individuals take ownership in the adoption process.